Real-world Chinese herbal medicine for Parkinson's disease: a hospital-based retrospective analysis of electronic medical records - Lyu, Shaohua; Zhang, Claire Shuiqing; Mao, Zhenhui; Guo, Xinfeng; Li, Zhe; Luo, Xiaodong; Sun, Jingbo; Su, Qiaozhen (Frontiers in Aging Neuroscience, 2024)
Background: Parkinson’ disease (PD) is a progressive neurodegenerative condition. Chinese medicine therapies have demonstrated effectiveness for PD in controlled settings. However, the utilisation of Chinese medicine therapies for PD in real-world clinical practice and the characteristics of patients seeking these therapies have not been thoroughly summarised. Method: The study retrospectively analysed initial patient encounters (PEs) with a first-listed diagnosis of PD, based on electronic medical records from Guangdong Provincial Hospital of Chinese Medicine between July 2018 and July 2023. Results: A total of 3,206 PEs, each corresponding to an individual patient, were eligible for analyses. Approximately 60% of patients made initial visits to the Chinese medicine hospital after receiving a PD diagnosis, around 4.59 years after the onset of motor symptoms. Over 75% of the patients visited the Internal Medicine Outpatient Clinic at their initial visits, while a mere 13.85% visited PD Chronic Care Clinic. Rest tremor (61.98%) and bradykinesia (52.34%) are the most commonly reported motor symptoms, followed by rigidity (40.70%). The most commonly recorded non-motor symptoms included constipation (31.88%) and sleep disturbance (25.27%). Integration of Chinese medicine and conventional medicine therapies was the most common treatment method (39.15%), followed by single use of Chinese herbal medicine (27.14%). The most frequently prescribed herbs for PD included Glycyrrhiza uralensis Fisch. (gan cao), Astragalus mongholicus Bunge (huang qi), Atractylodes macrocephala Koidz. (bai zhu), Angelica sinensis (Oliv.) Diels (dang gui), Rehmannia glutinosa (Gaertn.) DC. (di huang), Paeonia lactiflora Pall. (bai shao), Bupleurum chinense DC. (chai hu), Citrus aurantium L. (zhi qiao/zhi shi/chen pi), Panax ginseng C. A. Mey. (ren shen), and Poria cocos (Schw.) Wolf (fu ling). These herbs contribute to formulation of Bu zhong yi qi tang (BZYQT). Conclusion: Patients typically initiated Chinese medical care after the establishment of PD diagnosis, approximately 4.59 years post-onset of motor symptoms. The prevalent utilisation of CHM decoctions and patented Chinese herbal medicine products, underscores its potential in addressing both motor and non-motor symptoms. Despite available evidence, rigorous clinical trials are needed to validate and optimise the integration of CHM, particularly BZYQT, into therapeutic strategies for PD.